The histone demethylase Kdm5 controls Hid-induced cell death in Drosophila - Herz, Hans-Martin; Bergmann, Andreas (Frontiers in Cell Death, 2024)
We conducted an EMS mutagenesis screen on chromosome arm 2L to identify recessive suppressors of GMR-hid-induced apoptosis in the Drosophila eye. Through this screen, we recovered three alleles of the lysine demethylase gene Kdm5. Kdm5, a member of the JmjCdomain-containing protein family, possesses histone demethylase activity towards H3K4me3.Our data suggest that Kdm5 specifically regulates Hid-induced cell death during development, as we did not observe control of Reaper-or Grim-induced cell death by Kdm5. Interestingly, GMR-hid-induced apoptosis is suppressed independently of Kdm5's demethylase activity. Our findings indicate that Rbf and dMyc are necessary for Kdm5 mosaics to suppress GMR-hidinduced cell death. Moreover, Kdm5 mosaics failed to suppress apoptosis induced by a mutant form of Hid that is resistant to inhibition by Erk-type MAPK activity. Additionally, Kdm5 dominantly enhances the wing phenotype of an activated MAPK mutant. These results collectively suggest that Kdm5 controls Hid-induced apoptosis by regulating the Rbf, dMyc, and MAPK pathways.